Intrauterine thrombosis of umbilical artery – case report - Oliveira, Gustavo Henrique de; Dias, Cristiane de Moraes; Vaz-Oliani, Denise Cristina Mós; Oliani, Antonio Hélio (São Paulo Medical Journal, 2016)
CONTEXT: Umbilical cord thrombosis is related to greater fetal and perinatal morbidity and mortality. It is usually associated with umbilical cord abnormalities that lead to mechanical compression with consequent vascular ectasia. Its correct diagnosis and clinical management remains a challenge that has not yet been resolved. CASE REPORT: This study reports a case of umbilical artery thrombosis that occurred in the second half of a pregnancy. The umbilical cord was long, thin and overly twisted and the fetus presented severe intrauterine growth restriction. The clinical and histopathological findings from this case are described. CONCLUSIONS: This case report emphasizes the difficulty in diagnosing and clinically managing abnormalities of intrauterine life with a high chance of perinatal complications.